A CRITICAL DISCOURSE ANALYSIS AND ILLOCUTIONARY ACTS OF JOKO WIDODO’S SPEECH FOR THE 75th SESSION OF THE UNITED NATION GENERAL ASSEMBLY - Irani, Fatimah Aqillah (Universitas Muhammadiyah Semarang, 2021)
Discourse is a unit of language which it’s formed larger than a sentences used by the society in communication. Discourse also conducting social issues and used a specific language as information structures to deliver specific purposes. The present research designed based on descriptive qualitative research, employed Critical Discourse Analysis approach to investigate Joko widodo’s speech in the 75th session of United Nation General Assembly which aired on the 23 September 2020 virtually, focused on illocutionary act base on speech acts theory. The result showed that the speaker his speech not only addressed to the audience but also to the people in the world. The purposes of Jokoi’s speech are to congratulate the participant of United Nation for their efforts on making peaceful world and convey his hope for the freedom of all of country including Palestine. The speaker was answer the three concepts of question of critical discourse analysis, the speaker also produced the five types of illocutionary acts; representative, directive, commisive, expressive, and declaratives. However, the most illocutionary acts used by the speakers is Directive speech acts in his speech in order to inviting the participant and the people around the world to set a peaceful world together.